Studi Komparatif Tentang Penyelesaian Sengketa Tanah Hibah Kepada Anak Adopsi Di Desa Bangunan Palas Lampung Selatan (Hukum Islam dan Hukum Positif Indonesia) - R, Evi Septiana; Mubarokh, Titis; Fadhilillah, Nibras (ASAS, 2022)
The study is about the settlement of disputes over land grants to adopted children in the village of Gedung, Palas District, South Lampung Regency from the perspective of Islamic law and positive law in Indonesia. The focus of the research is how Islamic and Indonesian Positive Law view the settlement of land grant disputes adopted children. The purpose of this study is to find out how to resolve disputes in cases of grants to adopted children. In the research, the data collection method used by the author is field research by interview methods with parties related. After the data is collected, then it is analyzed using qualitative methods with an inductive thinking approach. The results of the study can be concluded that the resolution of land grant disputes to adopted children in Islamic law is by means of mediation. Mediation involves internal families and religious leaders as well as community leaders. In Islam, this means known as deliberation. Meanwhile, the settlement is carried out by way of dispute resolution outside the court known as Alternatif Penyelesaian Sengketa (APS)  or known as non-litigation.Keywords: Land Grant Dispute Resolution, Adopted Children, The mediation, Alternatif Penyelesaian Sengketa (APS) /non litigation.